The effectiveness of listening to memory songs in reducing depression in the elderly - Maria Kurni Menga; Ismarulyusda Binti Ishak; Wibowo Wibowo; M Khalid Fredy Saputra; Sarinah Sri Wulan; Dewi Nurhanifah (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Depression is a prevalent psychological issue among the elderly, often exacerbated by isolation and various physical and mental health challenges. As a non-pharmacological intervention, music therapy has shown potential in alleviating depressive symptoms. This study examines the effectiveness of listening to nostalgic songs in reducing depression among elderly residents. Methods: This study used a pre-experimental design with a one-group pretest-posttest approach. A total of 28 elderly participants who met the inclusion criteria were selected from a population of 43 individuals. The participants underwent a 20-minute intervention of listening to nostalgic songs, conducted six times over two weeks. Depression levels were measured using the Geriatric Depression Scale-15 (GDS-15) before and after the intervention. Data analysis was performed using the Wilcoxon test in SPSS version 25 to determine the significance of the intervention's effects. Results: The analysis revealed a significant reduction in depression levels after the intervention, with a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between pretest and posttest depression scores. This finding suggests that nostalgic music therapy effectively reduces depressive symptoms among elderly participants. Conclusions: The results support the hypothesis that listening to nostalgic songs can serve as an effective intervention for reducing depression in the elderly. Nostalgic music therapy can be considered a beneficial non-pharmacological approach to enhancing the psychological well-being of elderly individuals. Future studies with control groups and larger sample sizes are recommended to validate these findings further